GR_GERICHTE SKA 2004 39 vom 29. November 2004 , Lohnpfändung - GR Gerichte (2004)
Ersteigerung/betreibungsamtliche Besitzverschaffung | Leitentscheid, publiziert als PKG 2005 20\x3Cbr\x3E | Beschwerde 17 Abs. 1 SchKG